Dual inhibition of HERs and PD-1 counteract resistance in KRASG12C-mutant head and neck cancer - Ofra Novoplansky; Sankar Jagadeeshan; Manu Prasad; Ksenia M. Yegodayev; Divyasree Marripati; Raghda Abu Shareb; Yariv Greenshpan; Sooraj Mathukkada; Talal Ben-Lulu; Baisali Bhattacharya; Angel Porgador; Dexin Kong; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Basket clinical trials targeting the KRASG12C-mutation in solid tumors have shown initial promise, including in orphan KRASG12C head and neck cancer (HNC). However, development of resistance to KRASG12C-mutant-specific inhibitors (KRASG12Ci) remains a major obstacle. Here, we investigated the intrinsic (tumor-cell autonomus) and tumor-microenvironment (TME) mechanisms of resistance to the KRASG12Ci—MRTX849 and AMG510 in a unique syngenic murine KRASG12C-mutated HNC cell line. Methods Western-blotting was used for protein abundance and activation, overexpression, and ligand activation studies to verify the intrinsic mechanism of resistance to KRASG12Ci in KRASG12C-mutated HNC cell line, 4NQO-L. In vitro KRASG12C-acquired-resistant cells were developed from 4NQO-L (4NQO-L-AcR). MRTX849/lapatinib combination efficacy, and CD8+ T-cells depletion, were assessed in C57BL/6 J mice and supplementation of anti-PD-1 (αPD-1) to MRTX849/lapatinib was also performed in 4NQO-L– KRASG12Ci-senisitve and 4NQO-L-AcR tumors. Immunohistochemistry (IHC) and Immunoflourescence (IF) analyses were performed to profile the TME and programmed death-ligand 1 (PD-L1) expression in tumors. Results Activation and upregulation of EGFR and HER2/3 (pan-HERs) are the intrinsic mechanism of resistance to KRASG12Ci in 4NQO-L cells, and blocking pan-HERs signaling with lapatinib enhanced MRTX849 efficacy in vitro by inhibiting the MAPK and AKT/mTOR pathways. 4NQO-L-AcR upregulated the expression of pan-HERs, and lapatinib treatment re-sensitized 4NQO-L-AcR to MRTX849. In mice, MRTX849 showed a slight anti-tumor effect, but in combination with lapatinib a significant tumor growth delay was observed, but all tumors progressed over time. Histopathology analysis of the TME revealed infiltration of CD8+ T-cells after treatment combination, and these CD8+ T-cells play a key role in MRTX849/lapatinib efficacy. MRTX849/lapatinib treatment upregulated PD-L1 overexpression in both stromal and tumor cells, which presumably suppressed CD8+ T-cells and enabled immune escape and tumor progression. Supplementation of αPD-1 prolonged the progression-free survival of 4NQO-L-bearing mice treated with MRTX849/lapatinib. MRTX849/lapatinib treatment delayed tumor growth of 4NQO-L-AcR in mice; however, the percentages of CD8+ T-cells in 4NQO-L-AcR were low, and supplementation of MRTX849/lapatinib with αPD-1 did not improve the outcome. Conclusions Our study highlights the critical need for blocking both intrinsic and extrinsic mechanisms of resistance for the prolonged response and shows that such treatment is ineffective in KRASG12Ci-AcR tumors.